Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1161/01.cir.0000015076.37047.d9
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Ratio of Peak Early to Late Diastolic Filling Velocity as a Predictor of Mortality in Middle-Aged and Elderly Adults

Abstract: Background-With aging, left ventricular filling tends to decrease in early diastole, reducing the mitral ratio of peak early to late diastolic filling velocity (E/A). However, the prognostic significance of low or high E/A in older adults remains to be elucidated in population-based samples. Methods and Results-Doppler echocardiograms were analyzed in 3008 American Indian participants in the second Strong Heart Study examination who had no more than mild mitral or aortic regurgitation. Participants were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
268
4
16

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(302 citation statements)
references
References 30 publications
9
268
4
16
Order By: Relevance
“…18 The need of an echographic study in these patients is supported by several considerations: (1) previous investigation regarding the comparison between echocardiography and electrocardiography in the diagnosis of LVH showed that in populations with high prevalence of LVH, as patients with MS are, the former costs less for cases detected and gives a better prognosis of morbid events; 27 (2) Cuspidi et al 28 showed that ultrasound assessment not only of the heart but also of the carotid wall gives a more valid evaluation of the global cardiovascular risk in hypertensive patients without evidence of target organ damage; (3) patients with reduction of E on A, which is a predictor of the ventricular diastolic failure, are exposed to an increased risk of all-cause and cardiac mortality. 29 In addition, the present study has relevant implications also from the clinical research point of view. In particular, it will be interesting to compare the efficacy of pharmacological and nonpharmacological treatment or, probably better, of the combination of the two on the regression of LVH, particularly in patients with MS and high normal BP levels.…”
Section: Perspectivesmentioning
confidence: 81%
“…18 The need of an echographic study in these patients is supported by several considerations: (1) previous investigation regarding the comparison between echocardiography and electrocardiography in the diagnosis of LVH showed that in populations with high prevalence of LVH, as patients with MS are, the former costs less for cases detected and gives a better prognosis of morbid events; 27 (2) Cuspidi et al 28 showed that ultrasound assessment not only of the heart but also of the carotid wall gives a more valid evaluation of the global cardiovascular risk in hypertensive patients without evidence of target organ damage; (3) patients with reduction of E on A, which is a predictor of the ventricular diastolic failure, are exposed to an increased risk of all-cause and cardiac mortality. 29 In addition, the present study has relevant implications also from the clinical research point of view. In particular, it will be interesting to compare the efficacy of pharmacological and nonpharmacological treatment or, probably better, of the combination of the two on the regression of LVH, particularly in patients with MS and high normal BP levels.…”
Section: Perspectivesmentioning
confidence: 81%
“…Diastolic myocardial abnormalities are 129 associated with an increased risk of cardiovascular events and cardiac and all-cause mortality 130 50,51 . Early detection of myocardial dysfunction may provide an opportunity for patients to 131 modify their lifestyles, thereby affording the opportunity for primary prevention and reducing 132 mortality risk.…”
mentioning
confidence: 99%
“…The EDT undergoes less variation with aging and it is considered normal when <240 ms 17 . Using these criteria to diagnose diastolic dysfunction in the elderly population allowed the identification of those presenting a higher risk of death and congestive heart failure 10,18,19 .…”
Section: * Data In Absolute Numbers (Percentage) -Categorical Variablmentioning
confidence: 99%